Developing Employee Talent to Perform People Power - Kim, Warren (Business Expert, 2012)
People are an expensive, critical resource in any organization and can be a powerful source of sustained advantage. They profoundly affect other resources, including customers, brand reputation, intellectual property, and cash. They drive the growth or decline of these resources and possess attributes of their own—such as skills and knowledge—that must be carefully developed and nurtured. Despite this, leaders tend to focus on the softer aspects of people management, those that are the least easy to identify and infl uence, such as motivating, mentoring, and team-working—while ignoring the simpler fundamentals of how many they need, where, over time, to do what. Developing Employee Talent to Perform redresses the balance, providing a practical, fact-based approach to managing this most sensitive of resources. This book does the following: • shows leaders how to understand and manage the changes in their staff-base over time, in the light of often complex interactions between hiring, promotion, development, and attrition • explains where people connect to the tangible resources of the business, to help ensure they are deployed more effectively, getting the right number of the best people in the right places and adapting these deployments as the business changes through time • describes the mechanisms by which people and teams develop skills and shared capabilities, so that they can bring about substantially improved performance for the organization as a whole • provides a common language, in diagrams, words, and numbers, for leaders, HR professionals, and others in the management team to understand and communicate about how their staff resources are developing through time, ensuring that expensive and effort-intensive initiatives to develop the organization can be undertaken with confidence and support The book gives clear explanations and illustrations of the key concepts, with action checklists, key questions, and case examples. A strong understanding of how individuals interact with other resources to make the whole organization perform will help managers see how to act to maximize the effectiveness with which their organization operates. Improving performance through better decision making about your organization’s people is not just a matter for top management: Given the right tools, anyone with influence over how his or her enterprise works can make a difference. This book provides an original, rigorous, yet practical approach to developing organizational effectiveness that is long overdue.